Front Cover: Visible‐to‐UV Photon Upconversion in Nanostructured Chromophoric Ionic Liquids (ChemistryOpen 1/2020). Issue 1 (18th December 2019) - Hisamitsu, Shota; Miyano, Junji; Okumura, Keisuke; Hui, Joseph Ka‐Ho; Yanai, Nobuhiro; Kimizuka, Nobuo
Abstract : The Front Cover shows visible‐to‐ultraviolet (vis‐to‐UV) triplet‐triplet annihilation‐based photon upconversion (TTA‐UC) via triplet exciton diffusion in a chromophoric ionic liquid (IL). Chromophore moieties spontaneously form continuous arrays in non‐polar nano‐domains of the IL. The close arrangement of the chromophores in the IL allowed the effective diffusion of triplet excitons, resulting in the vis‐to‐UV TTA‐UC at a low excitation intensity. More information can be found in the Communication by Professor Nobuhiro Yanai et al. on page 15 in Issue 1, 2020 (DOI: 10.1002/open.201900304 ).